Fractional Order Proportional-Integral Controller Applied to a Back-To-Back Converters - Travieso-Torres, J (E D P SCIENCES, 2018)
The use of fractional order proportional-integral (FOPI) controllers, applied to back-to-back (BTB) power converters is proposed and studied in this paper. A comparative study with the integer order proportional-integral (PI) controllers, traditionally used for this purposes, is performed and the result are discussed. The BTB power converter is connected between a permanent magnet synchronous generator (PMSG) -which is moved by a turbine placed in line with a mineral pipeline for energy recovery purposes and the electrical network, to inject the recovered energy through a voltage control into the electrical network. Simulations under normal conditions (constant torque) as well as under variable torque variations are studied, representing different possible operating scenarios for the generator.